Association of MTHFR C677T polymorphism with schizophrenia and its effect on episodic memory and gray matter density in patients - Zhang, Yanling (2013)
Growing evidence suggests that the methylenetetrahydrofolate reductase (MTHFR) may play a role in the pathogenesis of schizophrenia. Recent studies suggested that the MTHFR 677T, as a risk allele, has an impact on brain activation and memory function in schizophrenia patients. To confirm further the association between this functional polymorphism and schizophrenia, we detected genotypes of MTHFR C677T polymorphism in 1,002 schizophrenic patients and 1,036 controls of Chinese Han population, by using direct DNA sequencing method. To explore further effects of MTHFR C677T polymorphism on memory and brain function in schizophrenia, 33 schizophrenia patients and 29 healthy participants were selected from above samples to be assessed with MRI scanning and episodic memory (EM) examination. The case - control association study results showed that the MTHFR C677T was associated with schizophrenia (χ(2) = 14.11, P = 1.74 × 10(−4), OR = 0.79; 95% CI = 0.70 – 0.89). We also found that the MTHFR 677T allele had a load-dependent effect on EM in schizophrenic patients, but not in healthy control participants. Further analysis on gray matter density (GMD) revealed significant diagnostic effects in bilateral frontal cortices, bilateral insula, left medial temporal cortex and bilateral occipital cortices, effects of MTHFR genotype in the right insula, right inferior frontal gyrus, right rolandic opercula, right parahippocampal gyrus and right medial temporal pole, and effects of genotype-diagnosis interaction in the right temporal gyrus. Our findings suggested that the MTHFR 677T allele might have effect on risk of schizophrenia, memory impairment and GMD changes in patients.